The Effect of Resilience and Professional Commitment on Reduced Audit Quality Behavior with Turnover Intention as an Intervening Variable - Adam Nugraha Hidayat; Poppy Sofia Koeswayo; Ahmad Zakie Mubarrok (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research was conducted based on the phenomenon of reduced audit quality behavior, a form of dysfunctional audit behavior that directly reduces audit quality. This issue represents one of the most significant internal challenges for BPK in preparing auditors capable of upholding core values of integrity, independence, and professionalism in conducting state financial audits. The purpose of this research is to determine the influence of resilience, professional commitment and turnover intention on reduced audit quality behavior, as well as to explore the role of turnover intention as an intervening variable in mediating the influence of resilience and professional commitment on reduced audit quality behavior. This research method is a quantitative method with a survey approach at BPK main office and BPK Representative. This research uses primary data obtained through filling out questionnaires online by 264 respondents who were sampled in the research. The data analysis method for this research is descriptive statistics and path analysis using the IBM SPSS Statistics 26 program. The research results show that resilience and professional commitment have a significant negative effect, while turnover intention has a significant positive effect on reduced audit quality behavior. Turnover intention as an intervening variable partially mediates the significant negative influence of resilience and professional commitment on reduced audit quality behavior.